Personal development potential of students with flat-valgus foot deformity in the process of adaptive physical education - Grigan, S.A.; Neshcheret, N.N.; Raskita, E.P.; Polin, R.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the attitude of students with flat-valgus foot deformity towards adaptive physical education classes. Methods and structure of the study. 15 students aged 18 to 25 with a diagnosis of flat-valgus foot deformity, who belong to a special medical group, participated in the scientific study. The study was conducted using an anonymous questionnaire consisting of 20 questions divided into four sections: physical abilities, psychological qualities, social skills, and emotional state. Results and conclusions. The survey revealed that regular physical exercise included in the adaptive physical education programme contributes to improving overall physical fitness; increased self-esteem and self-confidence may be associated with successful achievements and progress in physical exercise, which contributes to a sense of personal success; improved interaction with other students, increased comfort in the social environment, as well as increased social activity and integration into student life, which may be due to the fact that students from special groups begin to feel more confident.